Fostering Collaboration between Schools and Communities for Effective Management of Education in Imo State Secondary Schools - Nwankwo , Ijeoma Veronica (Kashere Journal of Education, 2025)
This study advocates for strengthened school community partnership to enhance entrepreneurship education administration in Imo State secondary schools for effective management of entrepreneurship education in secondary school administration in Owerri Education zone 1 of Imo state. The study argued that collaborative efforts betweens schools, local business, and communities can improve entrepreneurship skill promote innovation and drive economic growth. Two research questions and one null hypothesis guided the study. The study adopted a descriptive survey research. A sample of 190 made up of 120 principal/ teachers and 70 PTA executives was used for the study. The instrument used for data col1ccon was a 18- tem questionnaire. The research, questions were answered using mean and standard deviations while the null hypotheses were tested using t-test statistics. The findings of the study revealed that community members can actively participate in decision making of entrepreneurship, education administration. Also, it was revealed that community members can participate in provision of infrastructural facilities for entrepreneurship education administration, Based on the findings, the researchers recommended that government should encourage the operation of the school based management committee in the schools for smote school-community collaboration and that state government should through a possible medium sensitize all communities on the need for increased partnership in schools administration and provision of facilities for entrepreneurship education